Assessment of the COVID-19 Pandemic Impact on Agriculture and Food Security in Tajikistan - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
This dataset comprises household farm survey data gathered through a phone-based survey in 2020 to generate insights on the impact of the COVID-19 pandemic on rural farm households in Tajikistan. Data collection occurred between September and October 2020 across 12 districts in southwest Khatlon, part of USAID’s Zone of Influence. The sample includes 1,200 households—1,047 of which were part of the baseline survey from IFPRI's 2018 Assessment of Nutrition-Sensitive Value Chains in the Feed the Future Zone of Influence, with an additional 153 new households added due to attrition. Households were randomly selected from the baseline survey’s respondent roster, but the sample is not intended to be representative of the Zone of Influence. The survey's questionnaire covers a range of topics at the household level, including household composition, income, expenditures, migration, mobility, dietary diversity, and intrahousehold relationships, with a strong emphasis on agriculture. The agriculture module focuses on changes in household participation in agricultural activities, land use, access to and costs of inputs, male and female labor, machinery, market access, and information.